Molecular and phylogenetic characterization of honey bee viruses, Nosema microsporidia, protozoan parasites, and parasitic mites in China. Issue 2 (4th January 2013) - Yang, Bu; Peng, Guangda; Li, Tianbang; Kadowaki, Tatsuhiko
Abstract: China has the largest number of managed honey bee colonies, which produce the highest quantity of honey and royal jelly in the world; however, the presence of honey bee pathogens and parasites has never been rigorously identified in Chinese apiaries. We thus conducted a molecular survey of honey bee RNA viruses, Nosema microsporidia, protozoan parasites, and tracheal mites associated with nonnative Apis mellifera ligustica and native Apis cerana cerana colonies in China. We found the presence of black queen cell virus (BQCV), chronic bee paralysis virus (CBPV), deformed wing virus (DWV), Israeli acute paralysis virus (IAPV), and sacbrood virus (SBV), but not that of acute bee paralysis virus (ABPV) or Kashmir bee virus (KBV). DWV was the most prevalent in the tested samples. Phylogenies of Chinese viral isolates demonstrated that genetically heterogeneous populations of BQCV, CBPV, DWV, and A. cerana ‐infecting SBV, and relatively homogenous populations of IAPV and A. meliifera ‐infecting new strain of SBV with single origins, are spread in Chinese apiaries. Similar to previous observations in many countries, Nosema ceranae, but not Nosema apis, was prevalent in the tested samples. Crithidia mellificae, but not Apicystis bombi was found in five samples, including one A. c. cerana colony, demonstrating that C. mellificae is capable of infecting multiple honey bee species. Based on kinetoplast‐encoded cytochrome b sequences, the C. mellificae isolate from A. c. cerana represents a novel haplotype with 19 nucleotide differences from the Chinese and Japanese isolates from A. m. ligustica . This suggests that A. c. cerana is the native host for this specific haplotype. The tracheal mite, Acarapis woodi, was detected in one A. m. ligustica colony. Our results demonstrate that honey bee RNA viruses, N. ceranae, C. mellificae, and tracheal mites are present in Chinese apiaries, and some might be originated from native Asian honey bees. Abstract : Molecular and phylogenetic characterization of honey bee pathogens and parasites is conducted in China.